Penerapan Restorative Justice Kepolisian Terhadap Pencemaran Nama Baik dalam Dunia Digital - Hartanto, Hartanto; Budiarto, Djoko; Rhiti, Hyronimus (Universitas Proklamasi 45, 2022)
The National Police of the Republic of Indonesia is given a very broad authority in carrying out its duties as the main task of the National Police, among others Harkamtibmas, Protecting, Mengayami, Serving the community and Law Enforcement, in which it is also given another authority that is discretionary police an authority to perform actions based on the conscience of police members on duty and supported by the rules that exist in police institutions. The issue that will be discussed is whether the concept of Restorative Justice in accordance with the Circular letter of the Police Chief Number SE/2/II/2021 on Ethical Cultural Awareness to Realize a Clean Digital Space of Indonesia, Healthy, and Productive can be applied in accordance with the Law of the Republic of Indonesia No. 19 of 2016 Amendments to Law No. 11 of 2008 on Information and Electronic Transactions and Criminal Defamation regulated in the Criminal Code as an alternative to suppress cybercrime, but also must be able to as a deterrent effect in order to provide protection for the human rights of others.